Cross-center learning between CIMMYT and WorldFish - Bentley, Alison (2023)
“Now more than ever, we need to build greater resilience across our global food system,” said Alison Bentley, Director of Global Wheat Program at the International Maize and Wheat Improvement Center (CIMMYT), to introduce her part of a joint seminar between CIMMYT and WorldFish. The two CGIAR research centers may appear to have different focuses, but the pairing draws attention to many opportunities for intra-CGIAR collaboration to address the looming global food crisis.